Performance analysis of Svelte and Angular applications - Białecki, Gabriel; Pańczyk, Beata (Journal of Computer Sciences Institute, 2021)
The aim of this article is to check if the Svelte-based client part of a web application is more effective than the standard Angular approach. The article presents a comparison of page components rendering times on the basis of two test applications prepared in both frameworks. For the performance tests, scenarios were prepared in which the times of adding and removing a different number of page components were examined. Application tests were performed using the Selenium Webdriver package. The research results clearly showed that the new approach used for DOM manipulation (Svelte v.3.0) is more efficient than the standard solution used in Angular applications (v.10.2).